2012
DOI: 10.1088/2041-8205/755/1/l18
|View full text |Cite
|
Sign up to set email alerts
|

A NEW CEMP-s RR LYRAE STAR

Abstract: We show that SDSS J170733.93+585059.7 (hereafter SDSS J1707+58), previously identified by Aoki and collaborators as a carbon-enhanced metal-poor star (with s-process-element enhancements; CEMP-s), on the assumption that it is a main-sequence turn-off star, is the RR Lyrae star VIII-14 identified by the Lick Astrograph Survey. Revised abundances for SDSS J1707+58 are [Fe/H] = -2.92, [C/Fe] = +2.79, and [Ba/Fe] = +2.83. It is thus one of the most metalpoor RR Lyrae stars known, and has more extreme [C/Fe] and [B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…It is noteworthy that SDSS J1707+58 is now discovered to be an RR Lyrae star (Kinman et al 2012;see Stancliffe et al 2013 for a theoretical interpretation), instead of a main-sequence CEMP-s star . SDSS J1707+58 is one of the most metal-poor RR Lyrae stars known to date with [Fe/H] = −2.92, about 0.4 dex lower than that found by Aoki et al (2008).…”
mentioning
confidence: 99%
“…It is noteworthy that SDSS J1707+58 is now discovered to be an RR Lyrae star (Kinman et al 2012;see Stancliffe et al 2013 for a theoretical interpretation), instead of a main-sequence CEMP-s star . SDSS J1707+58 is one of the most metal-poor RR Lyrae stars known to date with [Fe/H] = −2.92, about 0.4 dex lower than that found by Aoki et al (2008).…”
mentioning
confidence: 99%
“…A few high resolution spectroscopic studies of elemental abundances of RR Lyrae stars are also found in the literature (Butler et al 1976(Butler et al , 1979Clementini et al 1995;Lambert et al 1996;Kolenberg et al 2010;For et al 2011;Kinman et al 2012;Govea et al 2014, Pancino et al 2014, submitted to MNRAS). For variables in globular clusters, individual metal abundances can be inferred from the accepted metallicities of the host clusters 2 .…”
Section: Metal Abundance Of Rr Lyrae Starsmentioning
confidence: 92%
“…The RR Lyrae stars observed for this pilot program, listed in Kinman et al (2012), were selected from the Hamburg/ESO objective-prism survey, cross-matched with previously recognized RR Lyraes. The benefit of drawing CEMP candidates from the Hamburg/ESO Survey (HES) is that (rather crude) preliminary estimates of [Fe/H] and [C/Fe] from their low-resolution spectra are available (Christlieb et al 2008).…”
Section: Target Selection and Observationsmentioning
confidence: 99%
“…Like the RR Lyrae variables studied in globular clusters, RR Lyrae field stars have been shown to exhibit properties of both Oo I and Oo II systems (Kinemuchi et al 2006), although the separation between the two populations is far less distinct. Following Kinman et al (2012), we study the Oosterhoff types of the CEMP RR Lyrae field stars in order to compare to classical Oosterhoff systems, as well as to explore how the presence of carbon in the atmosphere might affect the nature of the pulsation.…”
Section: Oosterhoff Classificationmentioning
confidence: 99%
See 1 more Smart Citation